THE CONTRIBUTION OF HUMAN CAPITAL AND STRUCTURAL CHANGE TO EAST JAVA’S ECONOMIC GROWTH: : DOES THE STRUCTURAL CHANGE BETTER THAN HUMAN CAPITAL? - Listiono (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2019)
This paper investigates the effect of human capital and structural changes on economic growth in East Java using panel data from 38 districts/cities during 2010-2015. The estimation results using the Generalized Method of Moment (GMM) Arellano-Bond show that health and education as indicators of human capital have a positive and significant effect on economic growth. In addition, structural changes as measured by the share of labor, especially in the industrial, construction, and services sectors have a positive and significant impact on economic growth. Interestingly, this study found evidence that structural changes have a greater effect than human capital.